Between Illusion and Loyalty: Deconstructing Parasocial Relationships in Celebrity Endorsement on Fan Loyalty Using a Grounded Theory Approach - Dewa Putu Yohanes Agata L. Sandopart (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The phenomenon of fans transforming from passive consumers into “digital warriors” who willingly sacrifice personal resources to defend their idols has created a new paradox in contemporary consumer behavior. Although previous research has confirmed the influence of parasocial relationships on purchase intentions, a critical gap lies in the inability of mainstream quantitative approaches to capture the transformational mechanism through which this imaginary relationship gradually crystallizes into transcendent loyalty that surpasses economic rationality. This study aims to construct a theoretical model explaining the transformation process of parasocial relationships into fan loyalty within the context of product endorsement. Using a grounded theory approach, this research involved 24 participants from three fan bases, including K-pop, football, and Indonesian musicians, through in-depth semi-structured interviews and digital document analysis. The findings produced a Three-Stage Parasocial Loyalty Transformation Model consisting of the Awakening phase, characterized by initial contact triggered by algorithms and identity seeking, the Immersion phase, marked by emotional and financial investment through digital rituals, and the Transcendence phase, where loyalty becomes naturalized as habitus. This study identifies a new concept referred to as “sacred loyalty,” a form of loyalty that adopts characteristics of devotion and actively rejects contradictory evidence. Theoretical implications include extending the parasocial relationship framework by incorporating dimensions of sacralization and digital collective engagement, while practical implications are directed toward marketers and media policymakers.